Hepatic Oxidative Stress, Apoptosis, and Inflammation in Broiler Chickens With Wooden Breast Myopathy - Xing, Tong; Pan, Xiaona; Zhang, Lin; Gao, Feng (Frontiers in Physiology, 2021)
Wooden breast (WB) syndrome has emerged as a global myopathy in modern commercial broiler chickens, mainly affecting the pectoralis major muscle. Recent evidence suggests WB myopathy is a systemic disease, which might be accompanied by other physiological disparities and metabolic changes. This study was conducted to systemically investigate the potential physiological changes in liver tissues as well as the possible mechanisms involved to enhance the understanding of the etiology. A total of 93 market-age Arbor Acres male broiler chickens were sampled and categorized into control (CON) and WB groups based on the evaluation of myopathic lesions. Liver samples were collected (n = 10 in each group) for histopathological evaluation and biochemical analyses. Results indicated that WB birds exhibited significantly higher plasma aspartate amino transferase, alkaline phosphatase and gamma glutamyl transpeptidase activities. Histopathological changes of hydropic/fatty degeneration, inflammatory cells infiltration, intrahepatic hemorrhages, elevated myeloperoxidase activity and overproduction of nitric oxide were observed in WB liver as compared with CON, suggesting the occurrence of liver injury in birds affected by WB myopathy. The WB group showed increased levels of reactive oxygen species, oxidative products, as well as enhanced antioxidant capacities in the liver. These changes were associated with impaired mitochondria morphology and mitochondrial dysfunction. WB myopathy also induced mitochondria-mediated hepatic apoptosis by upregulating levels of caspase3 and 9, altering the expressions of apoptotic B cell lymphoma-2 family regulators, as well as increasing the release of cytochrome c. The activation of nuclear factor kappa-light-chain-enhancer of activated B cells signaling enhanced the mRNA expression of downstream inflammatory mediators, contributing to the production of inflammatory cytokines in WB liver. Combined these findings suggest that hepatic disorders may be conjoint with WB myopathy in broiler chickens and indicating systemic physiological disparities and other metabolic changes accompanying this myopathy need further assessment.